Does trade openness affect economic growth in India? Evidence from threshold cointegration with asymmetric adjustment - Lingaraj Mallick; Smruti Ranjan Behera (Cogent Economics & Finance, 2020)
This paper investigates the long-run equilibrium relationship between economic growth and trade openness in India during the period 1960-2018 using the asymmetric error-correction model with threshold cointegration. To evaluate the robustness impact of trade openness on economic growth under different regimes, we divide the full sample period into two sub-periods, i.e., pre-trade reforms period 1960-1990, and post-trade reforms period 1991-2018. The study indeed confirms the evidence of asymmetric cointegration between economic growth and trade openness in India during the period under evaluation and over the different sub-periods. The estimated asymmetric error-correction model exhibits a different speed of adjustment in trade openness in response to positive and negative economic growth shocks in the short-run. More specifically, during the pre-reforms period, deviations from the long-run equilibrium due to a relative increase in economic growth have a lower speed of adjustment in comparison to deviations caused by a corresponding decrease in economic growth in India.
Keywords: C32; F62; O47; 330; economic growth; trade openness; threshold cointegration; error correctionmechanism